Induksi Kalus dari Antera Pisang Goroho (Musa acuminata L.) dengan Menggunakan 2,4-D dan BAP - Risna A. Onu; Jusna Ahmad; Febriyanti Febriyanti; Novri Youla Kandowangko; Devi Bunga Pagalla; Indriati Husain (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Callus induction is a critical stage in anther culture for supporting the propagation and genetic improvement of local banana cultivars. This study evaluated the effect of different combinations of 2,4-dichlorophenoxyacetic acid (2,4-D) and 6-benzylaminopurine (BAP) on callus induction from goroho banana (Musa acuminata L.) anthers. Observations were conducted for 30 days after induction, focusing on callus emergence time and morphological characteristics, including color and texture. The results demonstrated distinct responses among treatments. The combination of 1.5 ml 2,4-D and 1.5 ml BAP produced the fastest callus initiation with an average of 13.17 days after induction and generated friable callus with a pale yellow coloration, indicating high cellular activity. Lower growth regulator concentrations delayed callus formation, while higher concentrations promoted color changes associated with early tissue differentiation. No callus formation was observed in the absence of exogenous growth regulators. These findings highlight the importance of balanced auxin and cytokinin concentrations in regulating anther-derived callus induction and provide a physiological basis for further development of goroho banana anther culture systems.